DEVELOPMENT AND VALIDATION OF HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR DETERMINATION OF DAPAGLIFLOZIN AND ITS IMPURITIES IN TABLET DOSAGE FORM - GRACE A, CAROLINE; T, PRABHA; T, SIVAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present work is the development of new, sensitive, specific, and accurate high-performance liquid chromatographic method for the separation and determination of dapagliflozin and its impurities in tablet dosage form. Methods: The chromatographic separation of drug and its impurities was achieved using Hypersil BDS C18 column (250 mm × 4.6 mm, 5 μ) with mobile phase consisted of mobile phase-A (Buffer pH 6.5) and mobile phase-B (acetonitrile:water 90:10) by gradient program at a flow rate of 1 mL/min with ultraviolet detection at 245 nm. Results: Dapagliflozin and its impurities A, B, C, D, E, and impurity-F were successfully eluted at the retention time of 16.95, 2.72, 7.82, 10.58, 21.11, 30.37, and 34.36 min, respectively, with good resolution. The method was validated according to the international conference on harmonization guidelines. The validation results showed good precision, accuracy, linearity, specificity, sensitivity, and robustness. Conclusion: Successful separation and determination of dapagliflozin and its six impurities were achieved by the proposed method. The developed method can be applied for the routine analysis of dapagliflozin and its impurities in pharmaceutical formulations.